Epigenetic Regulation of Placental NR3C1: Mechanism Underlying Prenatal Programming of Infant Neurobehavior by Maternal Smoking?. Issue 1 (28th January 2016) - Stroud, Laura R.; Papandonatos, George D.; Salisbury, Amy L.; Phipps, Maureen G.; Huestis, Marilyn A.; Niaura, Raymond; Padbury, James F.; Marsit, Carmen J.; Lester, Barry M.
Abstract : Epigenetic regulation of the placental glucocorticoid receptor gene ( NR3C1 ) was investigated as a mechanism underlying links between maternal smoking during pregnancy (MSDP) and infant neurobehavior in 45 mother–infant pairs (49% MSDP‐exposed; 52% minorities; ages 18–35). The Neonatal Intensive Care Unit (NICU) Network Neurobehavioral Scale was administered 7 times over the 1st postnatal month; methylation of placental NR3C1 was assessed via bisulfite pyrosequencing. Increased placental NR3C1 methylation was associated with increased infant attention and self‐regulation, and decreased lethargy and need for examiner soothing over the 1st postnatal month. A causal steps approach revealed that NR3C1 methylation and MSDP were independently associated with lethargic behavior. Although preliminary, results highlight the importance of epigenetic mechanisms in elucidating pathways to neurobehavioral alterations from MSDP.